A TCM formula comprising Sophorae Flos and Lonicerae Japonicae Flos alters compositions of immune cells and molecules of the STAT3 pathway in melanoma microenvironment. (April 2019) - Liu, Yu-Xi; Bai, Jing-Xuan; Li, Ting; Fu, Xiu-Qiong; Guo, Hui; Zhu, Pei-Li; Chan, Yuen-Cheung; Chou, Ji-Yao; Yin, Cheng-Le; Li, Jun-Kui; Wang, Ya-Ping; Chen, Ying-Jie; et al.
Graphical abstract: Abstract: A traditional Chinese medicine (TCM) formula (SL) comprising Sophorae Flos and Lonicerae Japonicae Flos was used for treating melanoma in ancient China. We have previously shown that an ethanolic extract of SL (SLE) possesses anti-melanoma effects and suppresses STAT3 signaling in vitro and in vivo . STAT3 has been linked to the development of melanoma immunosuppressive microenvironment. In this work, we investigated whether SLE inhibits melanoma growth by reprogramming the tumor microenvironment in mouse and co-culture cell models. In B16F10 melanoma-bearing mice, we found that intragastric administration of SLE (1.2 g/kg) dramatically inhibited tumor growth. This observation was associated with the downregulation of protein levels of phospho-STAT3 (Tyr 705) and STAT3-regulated immunosuppressive cytokines, and mRNA levels of STAT3-targeted genes involved in tumor growth and immune evasion. We also observed increased Th, Tc and dendritic cells in the melanomas and spleens in SLE-treated mice compared to that in control mice. In a co-culture system composed of B16F10 cells and mouse primary splenic lymphocytes, it was found that SLE not only inhibited STAT3 activation in B16F10 cells, but also downregulated mRNA levels of STAT3-targeted genes in the splenic lymphocytes. In this co-culture setting, SLE decreased the levels of STAT3-regulated immunosuppressive cytokines, increased the percentages of Th, Tc and dendritic cells as well. Furthermore, effects of SLE on STAT3 phosphorylation, cytokine levels and immune cell subtype percentages were significantly weaker in the B16 STAT3C cells (stable cells harboring a constitutively active STAT3 variant STAT3C)/splenic lymphocytes co-culture system than in the B16 V cells (cells stably transfected with the empty vector)/splenic lymphocytes co-culture system, indicating that STAT3 over-activation diminishes SLE's effects. In summary, our findings indicate that reprograming the immune microenvironment, partially mediated by inhibiting STAT3 signaling, contributes to the anti-melanoma mechanisms of SLE. This study provides further pharmacological groundwork for developing SLE as a modern agent for melanoma prevention/treatment, and supports the notion that reprograming immunosuppressive microenvironment is a viable anti-melanoma strategy.